Digitalisation Impacting Marketing Strategies and Practices - Jaiwant Vincent, Sunanda (Ushus Journal of Business Management, 2023)
Digitalization through social media and the internet has altered the way marketers market their offerings and attract their customers and also the way consumers act, attend, buy and use the offerings and communications of the companies. Digitalization have revolutionized the marketing arena giving the organisations hordes of avenues and opportunities to lowers costs, raises brand awareness, and boosts sales. This article presents an insight into the impact of digitalization over the marketing strategies and practices. The study highlights the advent and role of advanced digital technologies like artificial intelligence, marketing using augmented reality, digital content management, mobile marketing and advertising, B2B marketing, electronic word of mouth, and related ethical concerns. The study evaluates how digital revolution affects businesses that employ digital marketing.